2019
DOI: 10.3390/v11121145
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Regulate Porcine Reproductive and Respiratory Syndrome Virus Infection via the AMPK-ACC1 Signaling Pathway

Abstract: Lipids play a crucial role in the replication of porcine reproductive and respiratory syndrome virus (PRRSV), a porcine virus that is endemic throughout the world. However, little is known about the effect of fatty acids (FAs), a type of vital lipid, on PRRSV infection. In this study, we found that treatment with a FA biosynthetic inhibitor significantly inhibited PRRSV propagation, indicating the necessity of FAs for optimal replication of PRRSV. Further study revealed that 5′-adenosine monophosphate (AMP)-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Although the inactivation processes were different in these two studies, it can be hypothesized that PRRSV inactivation would still allow the virus to attach to the epithelial cells, trigger receptor-mediated membrane signaling but not replication-dependent signaling. Regarding the AMPK pathway, it has been reported that host cells could antagonize PRRSV-2 infection via the activation of the AMPK-ACC1 signaling pathway [ 50 ]. Thus, inhibition of AMPK phosphorylation would help the virus in its multiplication cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Although the inactivation processes were different in these two studies, it can be hypothesized that PRRSV inactivation would still allow the virus to attach to the epithelial cells, trigger receptor-mediated membrane signaling but not replication-dependent signaling. Regarding the AMPK pathway, it has been reported that host cells could antagonize PRRSV-2 infection via the activation of the AMPK-ACC1 signaling pathway [ 50 ]. Thus, inhibition of AMPK phosphorylation would help the virus in its multiplication cycle.…”
Section: Discussionmentioning
confidence: 99%
“…MARC-145 and porcine monocyte-derived dendritic cells (mDCs) infected with PRRSV (North American strain P129-GFP) showed significant suppression by AMPK activators (sodium salicylate and U18666A) [55]. Recently, it was confirmed that AMPK activity increased at up to 1.5 dpi in PK-15 CD163 cells, that PAMs were infected with PRRSV (North American strain WUH3), that replication was inhibited through acetyl-CoA carboxylase 1 (ACC1), and that fatty acid biosynthesis was reduced by the AMPK activator A769662 [56]. In addition, proteins nsp2, nsp3, and nsp5 of PRRSV are also well known to induce cell membrane rearrangement for efficient replication [12], and it may interact with lipid metabolism such as AMPK signalling.…”
Section: Ampk Signalling and Lipid Metabolism In Response To Prrsv Inmentioning
confidence: 97%
“…An increased level fatty acid biosynthesis coupled with accumulation of free fatty acids that are associated with virus replication has been observed in host cells following CSFV infection ( Ma et al, 2019 ). Phosphorylated 5′-adenosine monophosphate-activated protein kinase induced by the infection of porcine reproductive and respiratory syndrome virus can inactivate the fatty acid biosynthesis pathway, playing an antagonistic role in the virus replication ( Long et al, 2019 ). Upon enterovirus A71 and coxsackievirus A16 infection, disturbed lipid homeostasis in the infected cells has been shown to be related to virus replication ( Yan et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%